Effects of examination stress on salivary biomarkers in Medical Laboratory Technology students / Farah Dayana Rosli ... [et al.] - Rosli, Farah Dayana; Sham Rambely, Azlin; Mohamed, Emida; Camalxaman, Siti Nazrina; Haron, Norhisham (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Salivary secretion is regulated by the sympathetic and parasympathetic nervous system which made it possible as useful biomarker of stress. This study aimed to determine the effects of academic examination stress on salivary cortisol, salivary immunoglobulin A (sIgA), and salivary alpha-amylase (sAA) in Medical Laboratory Technology (MLT) students. Five minutes unstimulated saliva samples were collected from thirty-nine students before and after a 1.5 hours written test. The concentration of selected salivary biomarkers were determined by enzyme-linked immunosorbent assay. Higher salivary cortisol levels were observed before the exam while for the IgA, the levels were higher after the exam (P<0.05). No significant differences were observed for alpha-amylase concentration before and after the exam. These findings suggest that the examination stress is associated with salivary cortisol and IgA which could be useful as an acute stress biomarker.